Corticosteroids for pain relief in sore throat: systematic review and meta-analysis - Hayward, G; Thompson, M; Heneghan, C; Perera, R; Del Mar, C; Glasziou, P (BMJ Publishing, 2009)
Objective: To evaluate whether systemic corticosteroids improve symptoms of sore throat in adults and children. Design: Systematic review and meta-analysis. Data sources: Cochrane Central, Medline, Embase, Database of Reviews of Effectiveness (DARE), NHS Health Economics Database, and bibliographies. Outcome measures: Percentage of patients with complete resolution at 24 and 48 hours, mean time to onset of pain relief, mean time to complete resolution of symptoms, days missed from work or school, recurrence, and adverse events. Results: We included eight trials, consisting of 743 patients in total (369 children, 374 adults). 348 (47%) had exudative sore throat, and 330 (44%) were positive for group A β-haemolytic streptococcus. In addition to antibiotics and analgesia, corticosteroids significantly increased the likelihood of complete resolution of pain at 24 hours (four trials) by more than three times (relative risk 3.2, 95% confidence interval 2.0 to 5.1), and at 48 hours (three trials) to a lesser extent (1.7, 1.3 to 2.1). Corticosteroids (six trials) reduced mean time to onset of pain relief by more than 6 hours (95% confidence interval 3.4 to 9.3, P<0.001), although significant heterogeneity was present. The mean time to complete resolution was inconsistent across trials and a pooled analysis was not undertaken. Reporting of other outcomes was limited. Conclusions: Corticosteroids provide symptomatic relief of pain in sore throat, in addition to antibiotic therapy, mainly in participants with severe exudative sore throat.